The Role of Teachers in Pedagogical Knowledge Practices and Approaches in Tamil Language Teaching - Asana, M.N.F.; Paunanthie, A. (University of Colombo, 2025)
This Study explores the role of Teachers in Pedagogical Content Knowledge (PCK) practices and approaches in Tamil language Teaching. In today's technologically advanced educational environment, teachers must create meaningful learning experiences for students and adjust their teaching methods accordingly. In this regard, knowledge-based teaching methods are a key tool for improving students' higher-level conceptual skills and language proficiency. This study is being carried out, focusing on their impact on student engagement and achievement. In an era of rapid technological advancement, effective integration of pedagogical strategies with ICT is essential for meaningful language learning. The primary objective is to investigate the role of teachers in relation to pedagogical content knowledge-based approaches and practices in Tamil language teaching, and to propose recommendations for improvement. The research employed a descriptive survey and qualitative design, involving 60 Tamil language teachers from 35 secondary schools in the Kandy district. Data were collected through interviews, classroom observations, and document analysis, and were analysed thematically. Findings revealed that although teachers possessed strong content knowledge, many relied predominantly on traditional lecture-based approaches. This reliance, along with limited ICT skills and inadequate resources, reduced classroom interactivity and hindered students’ learning outcomes. Teachers who applied activity-based strategies and incorporated technology were more successful in fostering student participation, motivation, and critical thinking. Significant challenges identified included time constraints, lack of technical facilities, and insufficient professional training. The study concludes that continuous professional development, targeted ICT training, and improved infrastructural support are crucial for enhancing the effectiveness of Tamil language teaching. Strengthening PCK practices will enable teachers to move beyond traditional methods and create learner-centred environments that improve achievement and language proficiency.
Keywords: Pedagogical knowledge; Tamil language teaching; teacher role